The Latin American Association for the Study of the Liver (ALEH) position statement on the redefinition of fatty liver disease. (January 2021) - Mendez-Sanchez, Nahum; Arrese, Marco; Gadano, Adrian; Oliveira, Claudia P; Fassio, Eduardo; Arab, Juan Pablo; Chávez-Tapia, Norberto C; Dirchwolf, Melisa; Torre, Aldo; Ridruejo, Ezequiel; Pinchemel-Cotrim, Helma; Castellanos Fernández, Marlen Ivón; et al.
Summary: The Latin American Association for the Study of the Liver (Asociación Latinoamericana para el Estudio del Hígado; ALEH) represents liver professionals in Latin America with the mission of promoting liver health and quality patient care by advancing the science and practice of hepatology and contributing to the development of a regional health policy framework. Fatty liver disease associated with metabolic dysfunction is of specific concern in the ALEH region, where its prevalence is one of the highest globally, second only to the Middle East. A recent consensus from an international panel recommended a new definition of fatty liver disease associated with metabolic dysfunction, including a shift in name from non-alcoholic fatty liver disease (NAFLD) to metabolic-associated fatty liver disease (MAFLD), and adoption of a set of positive criteria to diagnose the disease, independent of alcohol intake or other liver diseases. Given, the importance of this proposal, ALEH invited leading members of regional nations to come to a consensus on it from a local perspective. We reached a consensus to endorse the proposal that the disease should be renamed as MAFLD and that the disease should be diagnosed by the proposed simple and easily applicable criteria. We expect that this change in nosology will result in improvements in disease awareness and in advances in scientific, economic, public health, political, and regulatory aspects of the disease.